Les effets de la transterritorialité dans la migration guatémaltèque - Perla Petrich (Les Cahiers ALHIM)
The study adresses two topics : the first one focus on the departure from Guatemala, the dangerous trip through Mexico and finally, the difficult settlement and, in many cases, the return which may be voluntary or not.  The second topic focus on the transnational communities which are created in the settlement  country, the impact which they have on this country, on the transit country and on the  country of origin.